16th seduction - Patterson, James, 1947-; Paetro, Maxine (2017)
Still reeling from her husband's betrayal, Lindsay Boxer investigates a wave of possibly unnatural heart attacks claiming the lives of seemingly unrelated victims while assisting the prosecution of a bomber with a hostile defense team
Includes 18 page excerpt of Murder Games
Recreational Reading Collection
Keywords: Women's Murder Club (Imaginary organization) -- Fiction; Policewomen -- California -- San Francisco -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction; San Francisco (Calif.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction; Suspense fiction; Mystery fiction; Suspense fiction